2019
DOI: 10.1111/wusa.12426
|View full text |Cite
|
Sign up to set email alerts
|

Teacher social justice unionism and the field of industrial relations in the United States

Abstract: This article presents a critical discourse on the lack of scholarship and empirical studies on teacher social justice unionism in the field of industrial relations in the United States. It does so by pointing to union density, social justice unionism indicators in public education, and literature scarcity to consolidate its position to why teacher social justice unionism should be considered by researchers as a subject of academic inquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The term "social movement unionism" paired with "teachers" yielded 1830 references, a vast majority appearing in journals of labor studies, economics, and politics focusing on unions outside the U.S. "Social movement unionism" is often used interchangeably with "social justice unionism" (Bass , 2017) although they have different meanings (Gautreaux, 2019;Ross, 2007;Weiner, 2012), an important topic that takes us beyond the scope of this article. Dandala's (2019) review of research on social justice teacher unionism in "traditional industrial relations journals" confirms the paucity of research on social justice teacher unionism but also illustrates exclusion of educational research from labor studies. The review categorizes "Workplace: A Journal of Academic Labor," which we found as one of the major sources of writing about teachers unions in the U.S., as being outside the purview of "traditional industrial relations journals.…”
Section: Teacher Resistance To Neoliberal Educational Reformmentioning
confidence: 84%
“…The term "social movement unionism" paired with "teachers" yielded 1830 references, a vast majority appearing in journals of labor studies, economics, and politics focusing on unions outside the U.S. "Social movement unionism" is often used interchangeably with "social justice unionism" (Bass , 2017) although they have different meanings (Gautreaux, 2019;Ross, 2007;Weiner, 2012), an important topic that takes us beyond the scope of this article. Dandala's (2019) review of research on social justice teacher unionism in "traditional industrial relations journals" confirms the paucity of research on social justice teacher unionism but also illustrates exclusion of educational research from labor studies. The review categorizes "Workplace: A Journal of Academic Labor," which we found as one of the major sources of writing about teachers unions in the U.S., as being outside the purview of "traditional industrial relations journals.…”
Section: Teacher Resistance To Neoliberal Educational Reformmentioning
confidence: 84%
“…The small body of education and social sciences scholarship on social movement unionism has most directly attended to theories of power and change in unionisms. In Dandala's (2019) review of the literature, the author articulates social movement unionism as a broad category or approach, one that addresses social concerns that students and communities face. Likewise, within education research, scholars have articulated social movement unionism as a form of organizing that often transcends the distinct category of worker beyond only immediate economic interests and toward transforming social institutions via direct action (Peterson & Charney, 1999;Stark, 2019).…”
Section: The Rising Tide Of Social Movement Unionism: Tensions With Pmentioning
confidence: 99%
“…These reforms included but were not limited to cuts in public education funding, legal challenges to collective bargaining, and attempts to privatize and otherwise reform public education. This was the seed from which the current era of social justice union activity grew (Dandala 2019).…”
Section: A Brief Us History Of Educator Labor Organizingmentioning
confidence: 99%
“…Although the right for teachers to unionize and collectively bargain is important, what is significant for this examination into how labor actions can function as social justice intervention in education is the nature of the kinds of union and bargaining activity in which educators have been engaging for the last decade. To argue that teachers have not previously fought on behalf of justice and equity concerns is inaccurate (Dandala 2019;Peterson 1999;Rotteman et al 2015). Labor disputes writ large begin in conflict over fairness and equity matters.…”
Section: Nature Of Contemporary Educator Labor Actionsmentioning
confidence: 99%
See 1 more Smart Citation